2020
DOI: 10.1371/journal.pone.0236036
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the vaginal microbiota following antibiotic treatment for Mycoplasma genitalium, Chlamydia trachomatis and bacterial vaginosis

Abstract: The human vagina harbor a rich microbiota. The optimal state is dominated by lactobacilli that help to maintain health and prevent various diseases. However, the microbiota may rapidly change to a polymicrobial state that has been linked to a number of diseases. In the present study, the temporal changes of the vaginal microbiota in patients treated for sexually transmitted diseases or bacterial vaginosis (BV) and in untreated controls were studied for 26 days. The patients included 52 women treated with azith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Although limited by sample size, our findings are in agreement with other studies that showed a shift towards increased relative abundance of lactobacilli (mainly L. iners ) following 1g of oral azithromycin treatment. It has been shown that women with high relative abundance of L. iners were associated with increased susceptibility to C. trachomatis infection, suggesting that azithromycin treatment increase probabilities of transitioning to diverse disease-associated states or reinfection ( 40 , 41 ). Considering that both metronidazole and azithromycin favor increased relative abundance of unstable L. iners communities, there is a need to use Gardnerella specific-biofilm dissolving treatment, boosted with Lactobacilli-based live biotherapeutic products to restore an optimal vaginal microbiota after antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited by sample size, our findings are in agreement with other studies that showed a shift towards increased relative abundance of lactobacilli (mainly L. iners ) following 1g of oral azithromycin treatment. It has been shown that women with high relative abundance of L. iners were associated with increased susceptibility to C. trachomatis infection, suggesting that azithromycin treatment increase probabilities of transitioning to diverse disease-associated states or reinfection ( 40 , 41 ). Considering that both metronidazole and azithromycin favor increased relative abundance of unstable L. iners communities, there is a need to use Gardnerella specific-biofilm dissolving treatment, boosted with Lactobacilli-based live biotherapeutic products to restore an optimal vaginal microbiota after antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although these antibiotics are effective against BV-associated bacteria and somewhat relieve symptoms, the remission is usually temporary, and many patients relapse after treatment (Bradshaw et al, 2006;Hay, 2009;Mayer et al, 2015). The high recurrence rate (50%-67%) may be the result of the inability of antibiotics to eliminate the biofilm-associated bacteria of BV in vagina (Figure 2) (Swidsinski et al, 2008;Swidsinski et al, 2011;Javed et al, 2019;Ahrens et al, 2020;Verwijs et al, 2020). For example, Ahrens et al reported that G. vaginalis and other BVassociated bacteria are eradicated or are largely decreased in 58% of the patients treated with metronidazole.…”
Section: Treatmentmentioning
confidence: 99%
“…Meanwhile, none of these bacteria are eliminated in the remaining half of the patients. This phenomenon is attributed to the sheltering of G. vaginalis and other bacteria by biofilms (Ahrens et al, 2020). In addition, Swidsinski et al observed the persistence of G. vaginalis biofilms after oral metronidazole therapy (Swidsinski et al, 2008).…”
Section: Treatmentmentioning
confidence: 99%
“…The specific changes within the vaginal mucosal micro-environment that supports their expansion and colonisation remains poorly defined. We propose that the strategy for binding glycans has evolved more in vaginal confirmed and potential pathogens than in commensals, with the former producing a much larger variety of lectins and CBMs that enhances their capacity to adhere and bind to targets following disruption of the vaginal microbiome caused by menses 63 , contraceptives 64 , sexual activity 65 or antibiotic use 66 . Our findings are consistent with previous reports on the occurrence of a large number of lectin domains in different species of streptococci; these participate in the architecture of toxins, adhesins and pilins 67 .…”
Section: Discussionmentioning
confidence: 99%